2017
DOI: 10.3389/fendo.2017.00357
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod-Induced Increases in Bone Mineral Apposition Rate in Siberian Hamsters and the Involvement of Seasonal Leptin Changes

Abstract: The adipokine leptin regulates energy balance, appetite, and reproductive maturation. Leptin also acts on bone growth and remodeling, but both osteogenic and anti-osteogenic effects have been reported depending on experimental conditions. Siberian hamsters (Phodopus sungorus) have natural variation in circulating leptin concentrations, where serum leptin is significantly decreased during the short day (SD)-induced winter state. In summer long day (LD) photoperiods, appetite and body adiposity increase with ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
1
1
1
Order By: Relevance
“…Chickens in experimental group 2 exposed to low light showed a reduction in cortical thickness and density compared with the control group. However, this result conflicts with the study by Kokolski et al (2017), which showed that low light in fast-growing animals does not affect cortical thickness and tibial density.…”
Section: Histomorphometric Measurementscontrasting
confidence: 97%
See 1 more Smart Citation
“…Chickens in experimental group 2 exposed to low light showed a reduction in cortical thickness and density compared with the control group. However, this result conflicts with the study by Kokolski et al (2017), which showed that low light in fast-growing animals does not affect cortical thickness and tibial density.…”
Section: Histomorphometric Measurementscontrasting
confidence: 97%
“…Chickens in experimental group 2 had higher lengths of both zones (proliferative and hypertrophic) compared to control chickens. This result agrees with Kokolski et al (2017), who demonstrated that photoperiod significantly impacted bone growth characteristics, including growth plate size. The research revealed a clear increase in proliferative and hypertrophic zones, as well as a considerable increase in overall growth plate width under short-day conditions.…”
Section: Histomorphometric Measurementssupporting
confidence: 92%
“…Indeed, when female animals of this species are exposed to short photoperiods, they experienced ovarian function suppression. Furthermore, a long photoperiod is a potent environmental stimulus to increase bone mineral apposition rate in the skeleton of a closed-related species, the Siberian hamsters (Kokolski et al, 2017). Postmenopausal osteoporosis is a condition characterized by decreased bone mass associated with reduced serum levels of estrogens.…”
Section: Discussionmentioning
confidence: 99%